The Transnational in English Literature : Shakespeare to the Modern - Nayar, Pramod K. (Abingdon, Oxon Routledge, 2015)
Examines English literary history through its transnational engagements and argues that every period of English Literature can be examined through its global relations. English identity and nationhood is therefore defined through its negotiation with other regions and cultures.
Include Bibliography and Index.
Keywords: National characteristics, English, in literature -- Transnationalism in literature -- English literature